Postmodern Reading of Urdu Novel "Chakiwara Mein Wisal" - Bureeda Hamdani; Ghulam Farida (بازیافت)
Muhammad Khalid Akhtar is a renowned Urdu novelist. He has written many novels. Novel Chakiwara mein Wisal counts in his best novels. In this novel the author tries to address many social issues most importantly he uses various postmodern techniques. This article presents the implementation of these postmodern techniques like Pastiche, Metafiction, Irony, Participation of author, Black Humor, Historiographic Metafiction and Intertextuality. In the light of these debates it can be said that this novel is an important postmodern novel of Urdu literature.